Palatal manifestations of Langerhan cell histicytosis in pediatric age: a case report with review of literature - Singh, Ishwar; Negi, Sakshi; Dhingra, Shruti; Singh, Raghav; Mallya, Varuna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Langerhans cell histiocytosis (LCH) is characterised by multisystem disorder with various entities grouped together under same name. Oral cavity manifestations of this disease is yet to be explored. In oral cavity it can present with ulceration, swelling or osteolysis of underlying bone. Oral cavity involvement due to LCH might confuse the examining doctor resulting in misdiagnosis of such dreadful disease. So here we are reporting a case of LCH in a 4 years old female presented to us with ulceration over hard palate mucosa. Biopsy was taken from the ulcer site which was positive for LCH. On further examination and evaluation of the patient multisystem involvement was found with involvement of skull bone.